Opportunities and Challenges of Implementing Service Agreement under Public-Private-Partnership between the Government and Faith Based Organizations in Ilala Municipality, Dar es Salaam, Tanzania (Tanzania Medical Journal, 2023)
BackgroundAccess to essential health services is an important aspect of development.  Due to population increase and technological advancement, governments could no longer cater for the services needed. One of the solutions was to involve the private sector through Public Private Partnerships (PPPs) in the provision of the services. In 2007 Tanzania made a generic Service Agreement (SA) to govern PPPs in health sector. However, since its establishment, less is known on opportunities and challenges of its implementation in the provision of health services in Tanzania.Main ObjectiveTo assess the opportunities and challenges of implementing SA in Tanzania using a case study of Cardinal Rugambwa Mission Hospital (CRMH) and the Ilala Municipality in Dar es Salaam.MethodsA case study design using qualitative method of data collection was used. Data were collected by using an in-depth interview guide. Purposive sampling was used to select participants. The sample size was 23 participants based on the principle of saturation level of the information collected. Data were analyzed using a thematic analysis approach.ResultsThe opportunities of implementing SA in CRMH, Ilala Municipality include: the existence of guidelines and policies, Patients receiving some health services free of charges, availability of some services at reduced prices, presence of SA review meetings, good coordination, availability of supervision, training and mentorship opportunities, presence of political support, trust of the hospital by suppliers and trust between government and the hospital. The identified challenges in implementing SA include: - partial fulfillment of financial commitment, inadequacy deployment of Human Resources for Health (HRH) to CRMH by government, lack of transport for supervision and donor dependency.ConclusionThere are a number of available opportunities for partnering between the private sector and the government in the delivery of health services. However, for the PPP to achieve its desired objective of improving access to health services particularly to most vulnerable population such as women and children, there is a need for the two parties (private and public) to address the identified challenges such as partial fulfillment of financial commitment and inadequate deployment of HRH from the government to the private health facility as per SA.